Pengaruh Gaya Kepemimpinan Transformasional, Kompensasi dan Pemberdayaan Karyawan terhadap Kepuasan Kerja di RSU Muhammadiyah Siti Aminah Bumiayu - Deska Salsabila; Hengky Widhiandono; Akhmad Darmawan; Irawan Randikaparsa (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study was to examine and analyze the influence of transformational leadership styles, compensation and employee empowerment on employee job satisfaction at Muhammadiyah Siti Aminah Bumiayu General Hospital. This study uses a type of quantitative research. The population in this study were all nurses who worked at Muhammadiyah Siti Aminah Bumiayu General Hospital. Samples were taken using the slovin formula, a total of 107 employees at Muhammadiyah Siti Aminah Bumiayu General Hospital. The sampling technique in this study used the Simple Random Sampling (SRS) technique. The research instrument used a questionnaire. The analysis technique in this study used SPSS statistical analysis used for descriptive analysis, classical assumption test, linear regression analysis and hypothesis testing. The research results show that transformational leadership style, compensation and employee empowerment partially or simultaneously have a positive effect on job satisfaction at RSU Muhammadiyah Siti Aminah Bumiayu. The phenomenon of non-financial compensation or indirect compensation, such as holding intimate family gatherings, apparently does not reduce job satisfaction significantly. It is hoped that this research can become a reference for further research and be a consideration for companies in increasing job satisfaction so that it has a positive impact on the company's progress.